2013
DOI: 10.3402/fnr.v57i0.21836
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional adequacy of diets containing growing up milks or unfortified cow's milk in Irish children (aged 12–24 months)

Abstract: BackgroundGrowing up milks (GUM) are milk-based drinks with added vitamins and minerals intended for children aged 12–36 months. Few data are available on the consumption of GUM and their role in the diets of young children.ObjectiveTo determine the nutritional adequacy of two groups of 12–24-month-old Irish children by type of milk consumption (consumers or non-consumers of GUM).DesignUsing data from a cross-sectional study of Irish children, the National Pre-School Nutrition Survey (2010–2011), two groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 12 publications
6
50
0
3
Order By: Relevance
“…Two recently conducted observational studies compared the nutritional intakes of young children (1-2 years old) consuming YCF with those consuming cow's milk (skimmed, semi-skimmed or whole) [24,25]. Both studies showed that a relatively high proportion of cow's milk consumers had inadequate intakes of iron and vitamin D, and in one of the studies vitamin C, linoleic acid and alpha-linoleic acid also [25].…”
Section: Discussionmentioning
confidence: 99%
“…Two recently conducted observational studies compared the nutritional intakes of young children (1-2 years old) consuming YCF with those consuming cow's milk (skimmed, semi-skimmed or whole) [24,25]. Both studies showed that a relatively high proportion of cow's milk consumers had inadequate intakes of iron and vitamin D, and in one of the studies vitamin C, linoleic acid and alpha-linoleic acid also [25].…”
Section: Discussionmentioning
confidence: 99%
“…Data on nutrient intakes and biochemical status in young children aged 12-36 months from 19 countries were reviewed by the expert group [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41]. They are obtained from both national surveys and cross-sectional community-based surveys in Asia (Bangladesh, India, Indonesia, Malaysia, People's Republic of China, Philippines, Thailand and Vietnam), Australia, New Zealand, Europe (France, Ireland and Norway), Africa (Cameroon and South Africa), North America (Canada, Mexico and USA) and South America (Brazil).…”
Section: Nutrient Intakes and Status Of Young Children Aged 12-36 Monthsmentioning
confidence: 99%
“…В Ирландии (National Pre-School Nutrition Survey, 2010-2011) было проведено исследование питания детей в воз-расте 12-24 мес: среднесуточное общее потребление молока у них составило не менее 300 г, 29 детей потре-бляли напитки-последующие формулы для детей младшего возраста (FUF-YC) по 100 г/сут вместе с коровьим моло-ком, 56 детей -только коровье молоко [41]. Оказалось, что у детей, потреблявших обогащенные напитки, статисти-чески значимо ниже было поступление белка (38,1 против 43,7 г), насыщенных жиров (13,5 против 17,8 г) и вита-мина B 12 (3,6 против 5,4 мкг), а потребление углеводов (134,6 против 123,2 г), пищевых волокон (13,2 против 10,2 г), железа (10,4 против 5,9 мг), цинка (7,3 против 5,1 мг), витаминов С (118 против 58 мг) и D (9,2 и 2,1 мкг), наоборот, было выше.…”
Section: требования к обогащенным пищевым продуктам для детейunclassified